Water Inrush Mechanism of Fault Zone in Karst Tunnel under Fluid-Solid Coupling Field considering Effective Stress. (26th May 2022) - Huang, Cunhan; Dong, Wenhao; Cao, Zhengzheng; Wang, Yue; An, Gangjian; Chen, Huanqi; Jia, Yunlong; Pan, Qiuyu
Abstract : At present, the tunnel construction engineering is increasingly transferring to southwest mountainous areas with complex terrain and geological conditions in China and presents a trend of "large buried depth, long tunnel line, high stress, strong karst, high water pressure, complex structure and frequent disasters." Taking water inrush disaster of karst tunnel fault zone as the research object, an evolutionary mechanical model of rock damage under the coupling action of stress-seepage is proposed in this paper. Besides, based on Comsol Multiphysics numerical software, the tunnel excavation is simulated, and the stress field, seepage field, and rock damage during the excavation are analyzed; thus, the mechanical mechanism of water inrush disaster from tunnel fault in karst area is obtained. The research results indicate that the tunnel excavation is a dynamic construction process, and the construction disturbance redistributes the original rock stress field and changes the state of seepage field. With the increase of excavation steps, the contour distribution of vertical stress ratio near the tunnel face is a circle shape, indicating that the rock mass is obviously disturbed by excavation, and the ratio of principal stress difference of rock mass at arch crown and bottom plate is large. Besides, the fault fissures expand and penetrate under the influence of tunnel excavation disturbance, increasing the permeability of fault zone in karst tunnel. In addition, the water seepage erosion takes away the granular rock mass, and the lithology becomes more weaker, which makes it possible for the occurrence of water inrush disaster in karst tunnel. Therefore, the advanced geological prediction is important in tunnel construction in karst area. The research results can be treated as an important theoretical basis for the prevention and treatment for water inrush disaster of fault zone in karst tunnel.